2014
DOI: 10.1186/1472-6920-14-135
|View full text |Cite
|
Sign up to set email alerts
|

From board to bedside – training the communication competences of medical students with role plays

Abstract: BackgroundRole plays and standardized patients are often used in medical education and have proven to be effective tools for enhancing the communication skills of medical students. Most course concepts need additional time and teaching staff, and there are only a few studies about role plays in the preclinical segment.MethodsWe developed a highly consolidated concept for the curricular course of 2nd-year medical students, including ten role plays about five subjects: anamnesis, shared decision making, preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 26 publications
2
63
0
7
Order By: Relevance
“…Numerous studies conducted in medical students have demonstrated the effectiveness of role-play in teaching technical and communication skills in medical education. 6,7,10,11 In our study, we used the peer-role play technique that involved all the students to perform, learn and to personally experience patient concerns in front of their peers. Continuous feedback from peers gave the students an opportunity to sharpen their communication skills in a safe and supportive classroom environment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies conducted in medical students have demonstrated the effectiveness of role-play in teaching technical and communication skills in medical education. 6,7,10,11 In our study, we used the peer-role play technique that involved all the students to perform, learn and to personally experience patient concerns in front of their peers. Continuous feedback from peers gave the students an opportunity to sharpen their communication skills in a safe and supportive classroom environment.…”
Section: Discussionmentioning
confidence: 99%
“…This training module is designed both for individual and group study (Bishop et al, 2016). Possible ways for standardization of teaching communicative skills, assessment of certain communication factors before and after the courses of study, their integration into educational programs are proposed (Drdla & Loffler-Stastka, 2016;Kölfen, 2016;Modi et al, 2016;McKenzie, 2016;Cämmerer, Martin & Rockenbauch, 2016;Turner et al, 2016;Luttenberger et al, 2014;Mole, 2016;Hess et al, 2016).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…El desarrollo de políticas que mejoren la oferta de servicios y proteja la duración de la consulta ayudaría a aliviar, al menos en parte, uno de los inconvenientes que impide a los médicos implementar la TDC 35 . Resulta, además, fundamental el desarrollo de políticas que promuevan la incorporación de la enseñanza de destrezas comunicacionales, habilidades propias de TDC y atención centrada en el paciente, en las mallas curriculares de las escuelas de medicina, a modo de incorporar estos conocimientos de manera temprana y persistente en el entrenamiento de clínicos [34][35][36][37] . Recientemente, en 2015, la Asociación Americana de Diabetes (ADA) y la Asociación Europea para el Estudio de la Diabetes (EASD) reconocieron que la atención centrada en el paciente (y no en la enfermedad) es la forma de atención que mejor aborda la complejidad de enfrentarse a un paciente y su individualidad.…”
Section: Rol De Los Sistemas De Atención De Salud Las Políticas Y Guunclassified